¿Cuál universidad necesita nuestra América? - Barboza Lizano, Óscar Alfredo (2024)
On the centenary of the birth of the Latin Americanist intellectual Darcy Ribeiro, it is more necessary than ever to reflect on the idea of the Necessary University that he developed. At the crossroads of humanity, Darcy's idea leads us along the right path to achieve the required structural transformations in a Latin America that continues with many pending tasks since independence. It is proposed that the perspectives on unity, anti-imperialism and confrontation with which the idea of Latin America was founded by Bilbao, in 1856, should guide the prospective project of our America. The concept of Necessary University is inserted in this liberating project, reinforcing the Latin American identity/s through a true university institution, which responds to the nature of our America. This article seeks to look at ourselves as Latin America and the Caribbean from three dimensions: one, a cultural area; two, a periphery; and three, from unity. It proposes to answer the questions: Is the Necessary University the way to build the pending project of unity and authentic independence in our America? Is the universality of Ribeiro's idea consolidated with the founding of the National University in Costa Rica and the University of Brasilia?